Formation of Pancasila Morals in Children at SDN 1 Totobo, Pomalaa District, Kolaka Regency - Sahria, St.; Zakariah, M. Askari; Akbar, Muhammad (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aims to analyze the formation of Pancasila morals in students of SDN 1 Totobo through the integration of Pancasila values in the curriculum, extracurricular activities, and habituation in daily life. This research uses a qualitative method with a descriptive approach involving observation, interviews, and documentation as data collection techniques. The results showed that Pancasila values have been integrated in various subjects, especially Pancasila and Citizenship Education (PPKn), Religious Education, and Natural Sciences (IPA). In addition, extracurricular activities, such as Scouting, sports, and social activities, play an important role in instilling national values and students' moral character. Habituation in school life, such as flag ceremonies, prayers, community service, and discipline, has also proven effective in shaping Pancasila-based character. Supporting factors in the implementation of Pancasila values include school policies, the role of teachers as role models, and support from parents and the community. This study concludes that Pancasila moral formation at SDN 1 Totobo has been running well, but still needs strengthening in technology-based innovative strategies and parental involvement in student character education.